Biochemical analysis and bone remodeling in response to oophorectomy and aquatic training - Souza, Helena Ribeiro [UNESP]; Girol, Ana Paula [UNESP]; Schiaveto, Adriana Paula Sanchez; Geromel, Mairto Roberis; Iyomasa, Melina Mizusaki; de Arruda, Maurício Ferraz (FapUNIFESP (SciELO), 2016)
Objective: To investigate whether swimming could prevent bone loss and could be indicated to assist in treatment of osteoporosis. Methods: Female rats were divided into 4 groups (n=6), two of them were oophorectomized. Animals from two groups, one oophorectomized and another not oophorectomized, underwent aquatic training for eight weeks. After training, the animals were sacrificed and their blood was collected for calcium and alkaline phosphatase serum dosage; the femur was removed and subjected to radiological and histological densitometry analysis to assess bone loss and osteoclast counting on femoral head and neck. Results: Increase in serum calcium was not observed. There was an increasing activity of alkaline phosphatase in the oophorectomized groups. The radiographs suggest that there was a greater bone mass density in the trained groups. Concerning histology, the trained groups had better tissue structural organization than the sedentary groups. In the oophorectomized and sedentary group, higher presence of osteoclasts was observed a. Conclusion: Exercise and oophorectomy did not promote changes in serum calcium levels. The decrease of sex steroids caused by oophorectomy was responsible for severe bone loss, but swimming exercise was able to reduce this loss. Oophorectomy promoted the proliferation of osteoclasts and the exercise proved to be able to diminish it. Level of Evidence I, Experimental Study.
Keywords: Alkaline phosphatase; Calcium; Exercise; Oophorectomy; Osteoclasts; Osteoporosis; Radiography; Rats; Swimming